Estudo do conversor boost-flyback para sistemas fotovoltaicos - Varjão, Daniel da Silva (2021)
This work aims to study the boost-flyback converter for photovoltaic systems and the analysis of the converter implementation. The integration performed was the boost converter and the flyback converter. The topology used for the boost-flyback integrated converter was the series configuration, where the resulting voltage of the converter under analysis is the sum of the voltages of both converters.The built-in converter boost-flyback in the series topology is used for high voltage gain. The converter is designed for an output voltage of 200 Volts from a duty cycle of 0.55. With the duty cycle the converter did not reach the desired voltage, it was necessary to adjust the duty cycle to 0.66 in order to have the desired voltage. The voltage ripple designed for the converter is 5%, in the value of 10 Volts and the current ripple of 30% of the input current, in the value of 1.8919 Amperes. The voltage ripple at the output of each part of the converter met the design specifications, the current ripple was higher than projected, due to the resonance presented in the converter.The switch voltage between drain and source was 108 Volts, with some peaks reaching 142.5 Volts. The waveform between gate and source had negative peaks due to resonance in the converter, this can be explained by the high switching frequency of 100,000 Hertz in the converter.